Legal implications of conversion to Islam on civil marriage: narrative of converts in Malaysia - Mohd Al Adib Samuri,; Azlan Shah Nabees Khan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Due to a complex legal system in Malaysia, Muslim converts were left with no other option but to negotiate with their spouse to convert or file a petition for divorce in court. This study intends to explore the legal discourse and narratives of Muslim converts on the legal implications of their conversion to Islam, particularly in the cases of dissolution of civil marriage. To obtain the narratives of Muslim converts whom experienced this issue, this study employed in-depth semi-structured interviews with 9 participants (7 Indians, 1 Chinese, and 1 Bumiputera) whom are high-profile Muslim converts in urban Malaysia. This research has found that some participants in this study shared their narratives on how Malaysian law, both civil and Islamic law, has significant implications that affects converts’ marital lives and family dynamics. This study can become the foundation for an urgent call to revise the relevant laws, especially relating to the definition of People of the Book (Kitabiyyah), the period allocated for the non-Muslim spouse to convert to Islam, and the abolition of legal process of civil marriage dissolution in Shariah court. Beyond Malaysia, this study is important to depict how religious conversion impacts individuals, family dynamics and relations within a multi-ethnic and multifaith society.